A Complete Course on Theoretical Physics From Classical Mechanics to Advanced Quantum Statistics - Lindner, Albrecht (Undergraduate Lecture Notes in Physics,, 2018)
This textbook gives a basic introduction to theoretical physics. It deals with mechanics, electrodynamics, theory of relativity, quantum mechanics and statistical physics, thus covering all the standard disciplines of theoretical physics in a single volume. The material is presented in a concise style, enabling the reader to follow the central themes. Various excursions rarely found in other textbooks are designed to give deeper insight into interesting and current topics. A chapter on the mathematical background gives easy access to the other chapters and many exercises are included to support learning. The book is an ideal resource for advanced undergraduate and graduate students seeking to consolidate their knowledge.